2009
DOI: 10.1007/s11746-009-1503-3
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme‐Assisted Aqueous Extraction of Oil from Isolated Oleosomes of Soybean Flour

Abstract: Enzyme-assisted aqueous extraction of oil from isolated soybean oleosomes was evaluated as an alternative to the conventional organic solvent extraction. Three different processes: hydrolysis of oleosomes, thermal demulsification of the skim or the slurry, and destabilization of the cream by the churning butter process were examined to enhance the release of free oil from isolated oleosomes. The oil extraction involved incubating the oleosomes with either 0, 2.5 or 5% protease (Protex 6L Ò ) at 60°C, pH 9 for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…They were identical in size to the oleosomes in situ [1][2][3][4][5][6]31]. The isolated oleosomes were subjected to freeze/thaw or heating, and did not release free oil as would be expected for an oil-in-water emulsion stabilized by soy protein and lecithin [20,30,33,34]. Our results demonstrated that the scale-up of our fractionation process does not affect the size or and shape of isolated oleosomes.…”
Section: Microstructuressupporting
confidence: 51%
See 1 more Smart Citation
“…They were identical in size to the oleosomes in situ [1][2][3][4][5][6]31]. The isolated oleosomes were subjected to freeze/thaw or heating, and did not release free oil as would be expected for an oil-in-water emulsion stabilized by soy protein and lecithin [20,30,33,34]. Our results demonstrated that the scale-up of our fractionation process does not affect the size or and shape of isolated oleosomes.…”
Section: Microstructuressupporting
confidence: 51%
“…We focused on the recovery rather than the purification of oleosome fractions. We have already demonstrated that oil from isolated oleosomes may be quantitatively recovered [20].…”
Section: Introductionmentioning
confidence: 97%
“…The major quality traits that were determined were not only their chemical components, but also the mycotoxins or adulterants from outside. It has been recognized that chemical parameters, such as oil and saccharides (such as fructose, glucose, and lactose) in soybean flour and milk powder, can be successfully determined using enzyme‐assisted aqueous and high‐performance liquid chromatography (HPLC) (Chávez‐Servı́n and others ; Towa and others ). Other biological techniques based on sensitive wheat‐specific polymerase chain reaction system, restriction fragment length polymorphism (RFLP) analysis, and lab‐on‐a‐chip capillary gel electrophoresis (LOC‐CGE) have also been utilized for the quantitative detection of adulterant particles in food powders (von Büren and others ; Mayer and others ).…”
Section: Introductionmentioning
confidence: 99%
“…Enzyme preparations hydrolyse and rupture the cell wall constituents and improve the release of intracellular contents. AEE technology has been applied for oils extraction from seed crops, such as pumpkin (Jiao et al, 2014), oil palm fruit (Teixeira et al, 2013), bayberry (Zhang et al, 2012), peanut Jiang et al, 2010), watermelon , sesame (Latif & Anwar, 2011), flax (Long et al, 2011), wheat (Li et al, 2010), and soybean (Towa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%